Perlindungan Hukum Korban Kekerasan Psikis dalam Relasi Non-Perkawinan - Moh Fikri Fakhrizal M; Muh Jufri Ahmad (Media Hukum Indonesia (MHI), 2026)
Non-marital relationships, including dating and cohabitation, have become increasingly prevalent in modern society. Within these relationships, psychological violence may occur in various forms, such as verbal abuse, threats, emotional manipulation, gaslighting, excessive controlling behavior, and other actions that inflict mental suffering and psychological distress on victims. Despite the severe consequences of such violence, legal protection for victims of psychological abuse in non-marital relationships remains inadequate, as Indonesian positive law has yet to provide specific regulations governing the protection of victims outside the institution of marriage. This study aims to analyze the existing legal protection available for victims of psychological violence in non-marital relationships and to examine the urgency of establishing specific legislation to ensure comprehensive legal protection for such victims. The research employs a normative legal method using statutory, conceptual, and case approaches. The findings indicate that current legal protection primarily relies on general provisions of criminal law, human rights instruments, and regulations concerning witness and victim protection. However, these legal frameworks have not yet provided specific, comprehensive, and effective protection for victims of psychological violence in non-marital relationships. Therefore, the enactment of a dedicated legal framework governing the protection of victims of psychological violence in non-marital relationships is urgently needed to address the existing legal vacuum, ensure legal certainty, uphold human rights, and promote comprehensive justice and recovery for victims.